2019
DOI: 10.1111/tbj.13720
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐five years of change in the management of the axilla in breast cancer

Abstract: Sentinel lymph node (SLN) biopsy is now used worldwide. It has led to many changes in how we manage the axilla in patients with breast cancer. This review covers four areas of management of the axilla in breast cancer: assessing the clinically node-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Moreover, the addition of accessory sentinel nodes increased the mean number of sentinel nodes to 3.3 leading to the decrease of false negative rate to 4.9% which is around two times lower than in the NSABP B-32 study. Although no real consensus exists concerning the number of SLN to be excised, a common practice is to try to have an average number of nodes removed close to 3 (13). Indeed, Bonneau et al showed in 2015 an association between the excision of 3 sentinel nodes and improved survival outcomes in patient with breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the addition of accessory sentinel nodes increased the mean number of sentinel nodes to 3.3 leading to the decrease of false negative rate to 4.9% which is around two times lower than in the NSABP B-32 study. Although no real consensus exists concerning the number of SLN to be excised, a common practice is to try to have an average number of nodes removed close to 3 (13). Indeed, Bonneau et al showed in 2015 an association between the excision of 3 sentinel nodes and improved survival outcomes in patient with breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is relatively easier to manage this condition in a patient with only lymphadenopathy, such a condition that may develop after vaccination in a patient with newly diagnosed breast cancer can cause confusion in axillary staging, which is very important in breast cancer management, when the tumor is located in the same axilla as the breast tumor. ALN involvement in breast cancer patients negatively affects the prognosis of the disease and is an important factor that determines the clinical and surgical approach [ 11 , 12 ]. Assessment of ALN involvement in all newly diagnosed breast cancer patients is requisite.…”
Section: Discussionmentioning
confidence: 99%
“…With the defects of Halsted's radical mastectomy and further extensive radical surgery, we cannot but turn back to modi ed radical surgery and breast conserving surgery and SLNB later. 3,6,8,[10][11][12] The development of this road has burned a series of painful imprint step by step in progress to minimally invasive and functional treatment.…”
Section: Discussionmentioning
confidence: 99%